Evaluation of Wearable Technology in Dementia: A Systematic Review and Meta-Analysis - Cote, Alanna C.; Phelps, Riley J.; Kabiri, Nina Shaafi; Bhangu, Jaspreet S.; Thomas, Kevin “Kip” (Frontiers in Medicine, 2021)
Background: The objective of this analysis was to systematically review studies employing wearable technology in patients with dementia by quantifying differences in digitally captured physiological endpoints. Methods: This systematic review and meta-analysis was based on web searches of Cochrane Database, PsycInfo, Pubmed, Embase and IEEE between October 25-31st, 2017. Observational studies providing physiological data measured by wearable technology on participants with dementia with a mean age  50. Data were extracted according to PRISMA guidelines and methodological quality assessed independently using Downs and Black criteria. Standardized mean differences between cases and controls were estimated using random-effects models. Results: 48 studies from 18,456 screened abstracts (Dementia: n = 2,516, Control: n = 1,224) met inclusion criteria for the systematic review. 19 of these studies were included in one or multiple meta-analyses (Dementia: n = 617, Control: n = 406). Participants with dementia demonstrated lower levels of daily activity (standardized mean difference (SMD), -1.38; 95% CI, -1.61 to -1.16), and increases in total sleep time (SMD, 0.35; 95% CI, 0.17 to 0.54). They demonstrated decreased sleep efficiency (SMD, -0.42; 95% CI, -0.63 to -0.21) and greater intradaily circadian variability (SMD, 0.46; 95% CI, 0.27 to 0.65) than controls. Statistical between-study heterogeneity was observed, possibly due to variation in testing duration, device type or patient setting. Conclusions and Relevance: Digitally captured data using wearable devices revealed that adults with dementia were less active, demonstrated increased fragmentation of their sleep-wake cycle and a loss of typical diurnal variation in circadian rhythm as compared to controls.